2011
DOI: 10.1108/16605371111127233
|View full text |Cite
|
Sign up to set email alerts
|

MEDTOUR: a scale for measuring medical tourism intentions

Abstract: Purpose -The purpose of this paper is to use a theoretical model to create a scale to predict medical tourism (MT) intentions.Design/methodology/approach -The theory of planned behavior (TPB) model was applied to MT by creating a 49-item questionnaire and collecting data from a convenience sample of 453 undergraduate students enrolled in a university located in the USA. Factor analysis was used to evaluate the results, and yielded a MEDTOUR scale containing 29 items.Findings -A regression of the three variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 35 publications
6
50
1
1
Order By: Relevance
“…However, they differ on the sample location and size, the definition of intention, and the methods used. Reddy et al (2010) surveyed students from a Midwestern university (N ¼ 336) and Martin et al (2011) surveyed students from a university based on the West Coast (N ¼ 453). Reddy et al (2010) predicted the intention to learn more about medical tourism; they used a one-item intention score, three-item scale for attitude, and one-item scale for subjective norm and behavioral control, respectively.…”
Section: Review Of Tpb In Medical Tourism Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they differ on the sample location and size, the definition of intention, and the methods used. Reddy et al (2010) surveyed students from a Midwestern university (N ¼ 336) and Martin et al (2011) surveyed students from a university based on the West Coast (N ¼ 453). Reddy et al (2010) predicted the intention to learn more about medical tourism; they used a one-item intention score, three-item scale for attitude, and one-item scale for subjective norm and behavioral control, respectively.…”
Section: Review Of Tpb In Medical Tourism Researchmentioning
confidence: 99%
“…While student samples are frequently used for exploratory research, a more representative sample is appropriate for generalizing to the population. Martin et al (2011) investigated the factors predicting the intention to actually go overseas to receive a medical procedure. They applied a direct method of measurement and followed the theoretical structure proposed 168 Z. Ramamonjiarivelo et al My family and friends expect me to go overseas for medical treatment.…”
Section: Review Of Tpb In Medical Tourism Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Chen, Kung, Huang, Chen, and Pei (2012) studied the willingness and barriers of potential medical tourists from China to seek treatment in Taiwan. Martin, Ramamonjiarivelo and Martin (2011) developed MEDTOUR, which is a scale for measuring medical tourism intention. However, the respondents comprised a convenience sample of undergraduate students enrolled in a four-year state university programme.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study by Alam and Sayuti (2011) found that PBC influences the intention to purchase halal food. Martin, Ramamonjiarivelo and Martin (2011) found that PBC is an important factor that influences travel intention. However, Sentosa and Nik Mat (2012) examined the applicability of TPB in Internet purchase behaviour and concluded that PBC is not an important determinant of behavioural intention.…”
Section: Perceived Behavioural Controlmentioning
confidence: 98%